Animal, Herb, and Microbial Toxins for Structural and Pharmacological Study of Acid-Sensing Ion Channels - Osmakov, Dmitry I.; Khasanov, Timur A.; Andreev, Yaroslav A.; Lyukmanova, Ekaterina N.; Kozlov, Sergey A. (Frontiers in Pharmacology, 2020)
Acid-sensing ion channels (ASICs) are of the most sensitive molecular sensors of extracellular pH change in mammals. Six isoforms of these channels are widely represented in membranes of neuronal and non-neuronal cells, where these molecules are involved in different important regulatory functions, such as synaptic plasticity, learning, memory, and nociception, as well as in various pathological states. Structural and functional studies of both wild-type and mutant ASICs are essential for human care and medicine for the efficient treatment of socially significant diseases and ensure a comfortable standard of life. Ligands of ASICs serve as indispensable tools for these studies. Such bioactive compounds can be synthesized artificially. However, to date, the search for such molecules has been most effective amongst natural sources, such as animal venoms or plants and microbial extracts. In this review, we provide a detailed and comprehensive structural and functional description of natural compounds acting on ASICs, as well as the latest information on structural aspects of their interaction with the channels. Many of the examples provided in the review demonstrate the undoubted fundamental and practical successes of using natural toxins. Without toxins, it would not be possible to obtain data on the mechanisms of ASICs’ functioning, provide detailed study of their pharmacological properties, or assess the contribution of the channels to development of different pathologies. The selectivity to different isoforms and variety in the channel modulation mode allow for the appraisal of prospective candidates for the development of new drugs.